Ontogeny and shape change of the phacopid trilobite Calyptaulax. (November 2019) - Jacobs, Gabriel S.; Carlucci, Jesse R.
Abstract: Major transitions in trilobite ontogeny have historically been defined based on the number and distribution of trunk segments, and articulation between the trunk and cephalon. This study documents additional morphological change across the meraspid-holaspid transition on the Ordovician phacopid trilobite Calyptaulax strasburgensis . An extensive dataset of silicified cranidia and pygidia collected from the mid-Ordovician Edinburg Formation of Virginia was subjected to a series of multivariate analyses, with a primary focus on the intersections and termini of furrows. Multivariate regression of partial warp scores demonstrates statistically significant change in allometric growth patterns over the course of development. These changes are concentrated in earlier instars, but are coincident in cranidia and pygidia. This sharp decrease in the rate of allometry, present in both tagmata, is expressed as significant breakpoints derived from a segmented regression, with the largest portion of allometric change found in the pre-breakpoint individuals. The term holeidos is proposed to describe the completion of form during trilobite development, independent of the completion of the thorax. The most dramatic change in shape during this period of ontogeny includes lateral glabellar expansion through deflection of the axial and palpebral furrows, possibly reflecting a change in the feeding habit during later development. Other morphological changes include the development of a more angular appearance to the anterior portion of the glabella, and anterior migration of the pygidial anterior margin. The appearance of these growth patterns in Calyptaulax extends the temporal range of these changes, some of which have only been documented in Devonian phacopids.